Unraveling the Climate-Macro Conundrum: The Macroeconomic Impact of Climate Change in Eastern Africa - Geda, Alemayehu; Yimer, Addis; Demissie, Teferi Dejene; Radeny, Maren A.O.; Kassie, Girma; Tesfaye, Abonesh; Belay, Berhanu; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This study has empirically examined the macroeconomic impact of climate change in the East African region by focusing on Ethiopia, Kenya, Rwanda, Tanzania, and Uganda. It dealt with this effect comprehensively by focusing on economic growth, agricultural output, exports, and food security (using food supply and inflation). This is done using a suite of theoretical models from macroeconomic and macro-econometric literature. The analysis confirms that the effects of climate change in the region are real and present a macroeconomic danger to the economies of the five countries in the region. Specifically, the study found that climate change negatively affects the region's economic growth (total output), agriculture output, exports, food production and supply, and inflation dynamics. The study found several empirically specific effects of climate change. It, for instance, found climate change to reduce the annual GDP of the region by an average of about 7% (which varies from 2.5 in Tanzania to 15 in Ethiopia) by 2050, compared to a no-climate change scenario. The latter is found to have implications for food security in the region. The findings call for authorities in these economies to develop climate change coping and adaptation strategies not only for their own sake but also as part of their macroeconomic policy.